Project management best practices : achieving global excellence - Kerzner, Harold (Wiley, 2014)
Senior executives and project managers from more than 50 world-class companies offer their best practices for successful project management implementation The first two editions of the bestselling Project Management Best Practices helped project managers navigate the increasingly complex task of working within global corporations employing distant and diverse work teams. This new Third Edition includes the same valuable wealth of proven best practices, while following up on case studies from previous editions and offering new case studies on project management practices.